Mesoporous PbO nanoparticle-catalyzed synthesis of arylbenzodioxy xanthenedione scaffolds under solvent-free conditions in a ball mill. Issue 54 (30th September 2019) - Lambat, Trimurti L.; Chaudhary, Ratiram G.; Abdala, Ahmed A.; Mishra, Raghvendra Kumar; H. Mahmood, Sami; Banerjee, Subhash
Abstract : An efficient one-pot multicomponent protocol was developed for the synthesis of arylbenzodioxy xanthenedione scaffolds using mesoporous PbO nanoparticles as reusable catalyst under solvent-free ball milling conditions. Abstract : A protocol for the efficient synthesis of arylbenzodioxy xanthenedione scaffolds was developed via a one-pot multi-component reaction of aromatic aldehydes, 2-hydroxy-1, 4-naphthoquinone, and 3, 4-methylenedioxy phenol using mesoporous PbO nanoparticles (NPs) as a catalyst under ball milling conditions. The synthesis protocol offers outstanding advantages, including short reaction time (60 min), excellent yields of the products (92–97%), solvent-free conditions, use of mild and reusable PbO NPs as a catalyst, simple purification of the products by recrystallization, and finally, the use of a green process of dry ball milling.